Cisco CCIE routing and switching v5.0 configuration practice labs - Duggan, Martin (Cisco Press, 2014)
Cisco CCIE Routing and Switching v5.0 Configuration Practice Labs presents you with three full configuration lab scenarios in exam style format to echo the real CCIE Routing and Switching v5.0 lab exam. This publication gives you the opportunity to put into practice your own extensive theoretical knowledge of subjects to find out how they interact with each other on a larger complex scale. An "Ask the Proctor" section list of questions for each section helps provide clarity and maintain direction to ensure that you do not give up and check the answers directly if you find a task too challenging. After each lab, this eBook lets you compare configurations and routing tables with the required answers. You also can run through a lab de-brief, view configurations, and cut and paste configs into your own lab equipment for testing and verification. The point scoring for each question lets you know whether you passed or failed each lab. This extensive set of practice labs that sell for hundreds of dollars elsewhere helps you make sure you are fully prepared for the grueling CCIE lab exam experience